Modifi ed prosthetic rehabilitation of an enucleated pediatric patient with exposed intraocular implant - Rani Ranabhatt; Himanshi Aggarwal; Saumyendra V Singh; Vinit Shah (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2018)
Introduction: Retinoblastoma is one of the leading cancers in children below 5 years, leaving an ocular defect after enucleation. The loss of an eye requires early replacement so that socket contraction is minimal, growth of surrounding tissues is less retarted and the patient may return to a normal social life. Primary placement (at the time of enucleation) of hydroxyapatite intraocular implants is done in order to prevent volume defi cit and increase motility of the prosthesis. Exposure of this implant is a common complication where the amount of exposure usually decides the treatment modality. Large exposures requires surgical correction whereas small exposures may be managed conservatively. Patient: This article describes a pediatric patient with exposed hydroxyapatite intraocular implant managed successfully with a vaulted ocular prosthesis. Discussion: Simple prosthetic modifi cations leading to relief over exposed primary hydroxyapatite implant site may improve the patient's quality of life without the risks of secondary surgery. Conservative treatment with topical steroid and antibiotics along with prosthetic manipulation in form of vaulted ocular prosthesis or delayed fi tting of ocular prosthesis is recommended.